The worldwide transformation of higher education - Baker, David, 1952 Jan. 5-; Wiseman, Alexander W., 1968- (Bingley, UK : Jai, 2008)
Higher education worldwide, including the university and other related academic programs, is currently undergoing intensive change and transformation perhaps as no other time in its long history. One factor contributing to this rapid transformation is the global expansion of higher education at unprecedented rates. More of the world's population is continuing to higher education (and other forms of tertiary education) now than ever before. In fact, enrollment in institutions of higher education around the world is growing at a rapid rate. Some scholars have suggested that one reason for this rapid expansion is that the role of higher education has shifted over the last 50 years from an elite to a mass institution. As a result of this rapid expansion and shift in focus, the nature of students, faculty, the curriculum, and assessment is changing within the institution. And in society, the value of higher education and its impact on socioeconomic status, human capital, and technical innovation is changing as well. As a whole, the chapters in this volume in the "International Perspectives on Education and Society" series present a thoughtful discussion of the worldwide transformation of higher education from multiple perspectives. Contributors include Gaele Goastellec, David Turner, John C. Weidman, Adiya Enkhjargal, Christine Min Wotipka, Francisco O. Ramirez, Karin Amos, Lucia Bruno, Marcelo Parreira do Amaral, Mark S. Johnson, Christopher Collins, Robert A. Rhoads, Sunwoong Kim, Jun Li, Jing Lin, Chuing Prudence Chou, Philip G. Altbach, and Patti McGill Peterson.
Changes in access to higher education: from worldwide constraints to common patterns of reform? / Gaele Goastellec -- World university rankings / David Turner -- Corruption in higher education / John C. Weidman and Adiya Enkhjargal -- Women's studies as a global innovation / Christine Min Wotipka and Francisco O. Ramirez -- The research university in context: the examples of Brazil and Germany / Karin Amos, Lucia Bruno and Marcelo Parreira do Amaral -- Historical legacies of Soviet higher education and the transformation of higher education systems in post-Soviet Russia and Eurasia / Mark S. Johnson -- The World Bank and higher education in the developing world: the cases of Uganda and Thailand / Christopher S. Collins and Robert A. Rhoads -- Rapid expansion of higher education in South Korea: political economy of education fever / Sunwoong Kim -- China's move to mass higher education: an analysis of policy making from a rational framework / Jun Li and Jing Lin -- The impact of neo-liberalism on Taiwanese higher education / Chuing Prudence Chou -- America in the world: higher education and the global marketplace / Philip G. Altbach and Patti McGill Peterson.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Education, Higher; Education, Higher -- Cross-cultural studies; Higher & further education, tertiary education; Education, Higher